KEMAMPUAN SUAMI MEMBERI NAFKAH SEBAGAI SYARAT POLIGAMI - M. Yusuf Amin Nugroho (LPPM STAI DARUSSALAM LAMPUNG, 2012)
On the principle of marriage in Islam is monogamy. But in reality, due to various reasons, polygamy is still carried out. Polygamy in Islam is not an duty, but a choice. A husband permitted have polygamy should meet the requirements specified, one of which is having the ability to give a living. Requirement is also contained in UU No. 1 of 1974 Article 5 Paragraph (1) letter b. Then how to balance the law which is usually used judges court of religion, especially about the terms of the ability of the husband to give a living, for deciding the case of polygamy has been in accordance with Islamic law or not? This study wants to answer, the standard of whether the Court of Religion used to measure the ability of the husband in giving a living?